Chemotropic vs Hydrotropic Stimuli for Root Growth Orientation in Microgravity - Izzo, Luigi Gennaro; Romano, Leone Ermes; De Pascale, Stefania; Mele, Giacomo; Gargiulo, Laura; Aronne, Giovanna (Frontiers in Plant Science, 2019)
Understanding how plants respond to spaceflight and extraterrestrial environments is crucial to develop life-support systems intended for long-term human explorations. Gravity is a main factor influencing root development and orientation, typically masking other tropisms. Considering that reduced levels of gravity affect many plant responses in space, the interaction of other tropic stimuli in microgravity represents the frontier to be investigated aiming at life-support systems optimization. In this paper we report on MULTITROP (Multiple-Tropism: interaction of gravity, nutrient and water stimuli for root orientation in microgravity), an experiment performed on the International Space Station during the Expedition 52/53. Scientific aim of the experiment was to disentangle hydrotropism from chemotropism for root orientation in absence of the gravity stimulus. Among several species relevant to space farming, Daucus carota was selected for the experiment because of its suitability with the experimental hardware and setup. At launch site, carrot seeds were placed between two disks of inert substrate (one imbibed with water and the other with a disodium phosphate solution) and integrated into a hardware developed, refurbished and flight-certificated by Kayser Italia. Post-flight, a Ground Reference Experiment was performed. Root development and orientation of seedlings grown in microgravity and at 1g condition were measured through 3D-image analysis procedures after imaging with X-ray microtomography. Radicle protruded preferentially from the ventral side of the seed due to the asymmetric position of the embryo. Such a phenomenon did not prevent the achievement of MULTITROP scientific goal but should be considered for further experiments on radicle growth orientation in microgravity. The experiment conducted in space verified that the primary root of carrot shows a positive chemotropism towards disodium phosphate solution in the absence of the gravity stimulus. On Earth, the positive chemotropism was masked by the dominant effect of gravity and roots developed downward regardless of the presence/absence of nutrients in the substrate. Taking advantage of altered gravity conditions and using other chemical compounds, further studies should be performed to deepen our understanding of root chemotropic response and its interaction with other tropisms.